Departmental Recommendations for Tenure and Promotion: The Chair’s Letter - Denis M Medeiros; Rebecca Edmundson (Academic Chairpersons Conference Proceedings, 2016)
The department chair’s letter is likely the most important recommendation of a faculty for or against promotion and/or tenure. Elements to include in a letter and best practices will be provided. Sample letters of poor and excellent recommendations will be used interactively with the audience.
Keywords: Promotion and tenure; department chair; letter of recommendation; best practices; criteria